Impact of Heat Waves on the Well-Being and Risks of Elderly People Living Alone: Case Study in Urban and Peri-Urban Dwellings in the Atlantic Climate of Spain - Urtza Uriarte-Otazua; Zaloa Azkorra-Larrinaga; Miriam Varela-Alonso; Iñaki Gomez-Arriaran; Olatz Irulegi-Garmendia (Buildings)
This study investigates the impact of heatwaves on the thermal comfort and well-being of elderly individuals living alone during heatwaves, focusing on two contrasting residential typologies in the Atlantic climate of Spain: a dense urban area and low-density peri-urban setting. A mixed-methods approach was used, combining in situ environmental monitoring, adaptive comfort modelling, and user-centred data from surveys and interviews based on the De Jong-Gierveld Loneliness Scale. The results show that both dwellings exceeded recommended indoor temperature thresholds during heatwaves, especially at night, contributing to sleep disturbance, cardiovascular stress, and emotional discomfort. Despite 85% of participants indicating that outdoor activities help them to mitigate not-wanted loneliness, architectural barriers often hinder such engagement. Over half reported having no balcony or terrace, which may have further intensified social isolation. Field data collected during 2022 summer heatwaves recorded maximum daytime temperatures of 30 °C and night-time peaks of 28.7 °C, exceeding the 25 °C threshold. The adaptive comfort evaluation classified both cases as Class 4 (severe discomfort). The urban dwelling showed consistent moderate discomfort (Category 3), likely due to poor ventilation and urban heat island effects. The peri-urban case, despite lacking the heat island influence, showed worse thermal conditions, especially during the day. Architectural barriers, poor thermal performance, and the lack of semi-outdoor spaces may exacerbate isolation among elderly people during extreme heat events.